Analisis Diagnosis Organisasi dan Kesediaan Terhadap Perubahan di Kalangan Eksekutif Dalam Industri Sains dan Teknologi - Nor Zaneedarwaty, Norman (2012)
This study aims to analyze the organizational diagnosis among executives in the fields of science and technology. This study was also to determine whether the characteristics found in science and technology organization that is the purpose, structure, leadership, relationships and helpful mechanisms of assistance relating to the readiness to change to achieve a common vision, linking the organization with its environment and provide strategic leadership in preparation to become a developed country. A total of 106 respondents participated in this study. The results showed that the level of organizational diagnosis is high to all the features including the attitude towards change. Regression analysis showed that the six organizational characteristics significantly correlated with readiness to change. Thus, executives in the fields of science and technology can be considered ready and prepared towards the process to be a developed countries.